Progress in endoscopy: areas of current interest and topics to watch out for - Rösch, T. (Endoscopy, 2012)
The past few years have seen a shift in focus for endoscopy research. For example, there has been a halt in the apparent revolution of natural orifice transluminal surgery (NOTES), which was long considered the most important innovation in flexible endoscopy. Other trends such as endoscopic histology are slowing down and not progressing into clinical practice. In general, the quality of endoscopic research needs to be improved, particularly in the field of diagnostics and imaging 1. Nevertheless, progress in some areas continues, albeit at a slower pace than we might like. In this review the areas of current interest are reviewed with reference to the most relevant areas of progress in recent years.